Religious landscape of Vilnius: a phenomenological glance - Nikiforova, Basia (Creativity Studies, 2011)
The traditional religious landscape is changing considerably, and the current religious landscape exhibits a remarkable variety. The religious landscape was shifting. Today in Europe there are three general trends – secularization, new spirituality and immigrant religions such as Islam, Buddhism, Hinduism additional to Judeo-Christian tradition. Phenomenological approaches are crucial for developing new and deepening existing modes of cooperation between dissimilar cultures and religions. Using phenomenological approach we look on religious landscape of Vilnius as pluralistic from the two general views: old historical, traditional source and nowadays the increasing diversity. The article includes a short discussion about definition of ‘religious landscape’ and the possibilities of its interpretation. Using definition epochē from phenomenological point of view we conclude that religious landscape of Vilnius is pluralistic.Vilniaus religinis peizažas: fenomenologinis žvilgsnisSantrauka. Tradicinis religinis peizažas kinta labai pastebimai, o dabartinis demonstruoja ypač didelę įvairovę. Nūdien Europoje vyrauja trys bendros tendencijos – sekuliarizacija, naujasis dvasingumas ir imigrantų religijos, tokios kaip islamas, budizmas, iniduizmas greta judaistinės-krikščioniškosios tradicijos. Remdamiesi fenomenologiniu požiūriu, žvelgiame į religinį Vilniaus peizažą kaip į pliuralistinį, atsiveriantį iš dviejų bendrų perspektyvų: senoji istorinė, tradicinė versmė ir nūdien augantis skirtingumas. Straipsnyje imamasi trumpos diskusijos „religinio peizažo” tema ir apie šio apibrėžimo interpretavimo galimybes. Pasitelkiant sąvoką epochē, fenomenologinio mąstymo perspektyvoje prieinama išvada, kad Vilniaus religinis peizažas yra pliuralistinis.Reikšminiai žodžiai: epochē ir eidetinis matymas, fenomenologinis požiūris, religinis peizažas,  sacrum.